2011
DOI: 10.1590/s0103-50532011000400018
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Analysis of Essential Oils from Ocotea gomezii W.C. Burger and Ocotea morae Gómez-Laur. (Lauraceae) Collected at "Reserva Biológica Alberto M. Brenes" in Costa Rica and their Cytotoxic Activity on Tumor Cell Lines

Abstract: A composição química dos óleos essenciais obtidos de folhas, cascas e troncos de Ocotea gomezii e O. morae de populações silvestres da Costa Rica, está sendo descrita pela primeira vez. Os óleos de O. gomezii são constituídos principalmente por sesquiterpenóides enquanto os de O. morae apresentaram mono-e sesquiterpenóides na mesma proporção. A análise da composição química por CG/EM e CG/DIC resultou na identificação de 166 componentes, correspondente a 89,4-98,1% dos óleos totais. Quando comparada a atividad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 31 publications
(42 reference statements)
0
20
0
Order By: Relevance
“…These values are higher than those of the commercial herbicide at the same concentrations. These compounds isolated from O. pulchella have shown cytotoxic activity on tumor cell lines (CCF‐STTG1, Hep3B, HepG2, H‐460, AGS, N‐87, SW‐620, MCF‐7, and VERO), of which astrocytoma cells were the most resistant . If therapeutic concentrations have been achieved in target tissues, it has been demonstrated that these components may be useful in the treatment of age‐related inflammatory conditions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These values are higher than those of the commercial herbicide at the same concentrations. These compounds isolated from O. pulchella have shown cytotoxic activity on tumor cell lines (CCF‐STTG1, Hep3B, HepG2, H‐460, AGS, N‐87, SW‐620, MCF‐7, and VERO), of which astrocytoma cells were the most resistant . If therapeutic concentrations have been achieved in target tissues, it has been demonstrated that these components may be useful in the treatment of age‐related inflammatory conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Some species of this genus are used in popular medicine due to their antirheumatic, purgative, and tonic properties, and for the treatment of stomach disorders and abscesses , among other uses. The Lauraceae family is known to contain high levels of essential oils, which are mainly present in the leaves and have different reported biological activities . Other species are considered to be aromatic and they are therefore used in perfumery and flavorings .…”
Section: Introductionmentioning
confidence: 99%
“…These compounds were found in the essential oil fromO.nutans which reveals the close chemotaxonomic relationship between O. nutans and other species of Ocotea belonging to the first group of chemical diversity (one whose species contain terpenes compounds). This is typical of the essential oils of several Ocotea species from South America (Chaverri et al, 2011).…”
Section: Chemical Composition Of the Essential Oilmentioning
confidence: 63%
“…however, the chemical analysis of O. duckei and O. glomerata enables the inference of qualitative and quantitative differences between the essential oils. The chemical profile rich in monoterpenes and sesquiterpenes characterized in the oils from the species of Ocotea that occur in the state of Pernambuco is typical of essential oils from some species of Ocotea in South America (Chaverri et al 2011). Table II displays the results of the fumigation and residual contact bioassays with the Ocotea oils.…”
Section: Chemical Composition Of Ocotea Oilsmentioning
confidence: 99%
“…These oils are extracted from different parts of the plant and the main chemical classes found are monoterpenes (Olivero-Verbel et al 2010), sesquiterpenes, diterpenes (Setzer et al 2006, Takaku et al 2007, Yamaguchi et al 2013) and phenylpropanoids (Oltramari et al 2004). Studies on the biological properties of these essential oils reveal a broad spectrum of activity, including antimicrobial (Leporatti et al 2014, Farago et al 2010, anti-inflammatory, cytotoxic, antioxidant (Destryana et al 2014, Chaverri et al 2011) and molluscicidal (Coutinho et al 2007) properties, including insecticidal action against arthropods of medicinal interest, such as Aedes aegypti (Menut et al 2002), and agricultural interest, such as Sitophilus zeamais (Mossi et al 2013). To date, however, no studies have addressed the acaricidal activity of these oils.…”
Section: Introductionmentioning
confidence: 99%